2019
DOI: 10.1039/c9sc03747k
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-catalyzed hydroxymethylarylation of terpenes with formaldehyde and arenes

Abstract: Terpenes, consisting of isoprene monomer units, represent a family of naturally abundant compounds. The difunctionalization of terpenes is highly appealing yet remains challenging, since the multiple unbiased C]C bonds of terpenes lead to difficulty in controlling the regioselectivity. Herein, a cobalt(III)-catalyzed C-H activation strategy has been developed to facilitate hydroxymethylarylation of terpenes with formaldehyde and arenes with high chemo-and regio-selectivities. These (chemo-and regio-) selectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…According to above observations and previous reported studies, [ 14–22 ] a plausible catalytic cycle is proposed (Scheme 5). First, [RuCl 2 ( p ‐cymene)] 2 is converted by AgSbF 6 to the catalytically active ruthenium species I , which reacts with amide 1 to generate a five‐membered ruthenium intermediate II through chelate directed C–H activation.…”
Section: Figuresupporting
confidence: 58%
See 1 more Smart Citation
“…According to above observations and previous reported studies, [ 14–22 ] a plausible catalytic cycle is proposed (Scheme 5). First, [RuCl 2 ( p ‐cymene)] 2 is converted by AgSbF 6 to the catalytically active ruthenium species I , which reacts with amide 1 to generate a five‐membered ruthenium intermediate II through chelate directed C–H activation.…”
Section: Figuresupporting
confidence: 58%
“…Our study was intrigued by a previously reported procedure for the synthesis of 3‐unsubstituted phthalides from benzamides by Faigl, Volk and co‐workers, [ 13 ] involving ortho ‐lithiation, formylation, reduction and lactonization processes (Scheme 1c). Encouraged by the advances in the ortho ‐hydroxymethylation with paraformaldehyde via transition metal catalyzed C–H activation (e.g., ruthenium catalysis by Zhou, [ 14 ] Ding, [ 15 ] Wu, [ 16 ] and Kim [ 17 ] with pyridyl or pyrimidinyl as the directing group, rhodium catalysis by Kim [ 18 ] with azobenzene as substrate, manganese catalysis by Glorius [ 19 ] with pyridyl or pyrimidinyl as the directing group, cobalt‐catalyzed hydroxymethylarylation of terpenes with formaldehyde and arenes by Chen [ 20 ] ) and recent progress in the synthesis of 3‐substituted phthalides from benzamides and aldehydes by rhenium‐ [ 21 ] and rhodium‐catalysis, [ 22 ] we proposed that it might be possible to prepare 3‐unsubstituted phthalides in a single step by a sequential transition‐metal‐catalyzed ortho ‐hydroxymethylation and intramolecular lactonization strategy.…”
Section: Figurementioning
confidence: 99%
“…In this context, we set out to exploit a catalytic system to achieve regioselective coupling of isoprene, formaldehyde and 2-arylpyridines. 23 It was found that homoallylic alcohols 7 were afforded with exclusive regioselectivities when Cp*Co(CO)I 2 was employed as a catalyst with HOAc and AgSbF 6 as additives (Scheme 4). The electronic and steric factors of the substituents on the phenyl ring had no sig-…”
Section: Catalytic Coupling Of Formaldehyde Arenes and Isoprenementioning
confidence: 99%
“…Regarding the use of the widely available alkylbromides as precursors for carbocation intermediates in the Ritter reaction, which nucleophile would display stronger affinity toward carbocation, bromides or nitriles? Intrigued by the aforementioned issue and our long-standing interests in functionalization of alkenes ( Ji et al., 2019 ; Jiang et al., 2021 ; Kuai et al., 2020 ; Min et al., 2021 ; Yang et al., 2019 ), we sought to develop photo-induced three-component Ritter reaction of alkenes with alkylbromides and nitriles. Herein, we demonstrated an unprecedented role of fluoride salts for the enhancement of Ritter reaction and inhibition of ATRA ( Scheme 1 C).…”
Section: Introductionmentioning
confidence: 99%